A REVIEW ON EMULGELS-A NOVEL APPROACH FOR TOPICAL DRUG DELIVERY - Begum, S. Gousia; Chetty, C Madhusudan; Pavithra, B; Akhila, B.; Gayathri, C.; Ruksar, S.; Sravani, T.; Voleti, Vijay Kumar (Asian Journal of Pharmaceutical Research and Development, 2019)
Emulgels have emerged as one of the most interesting topical delivery system as it has dual release control system i.e. gel and emulsion. The major objective behind this formulation is delivery of hydrophobic drugs to systemic circulation via skin. A unique feature of topical drug delivery is the direct accessibility of the skin as a target organ for the diagnosis and treatment. When gel and emulsion are used in combined form the dosage form are referred as Emulgel. This may be proving better stability and release of drug than simply incorporating drugs into gel base. Other novel approaches like niosomes and liposomes are of nano size and due to vesicular structures may result in leakage and result in lesser entrapment efficiency. But gels due to vast network have comparatively better loading capacity.